Syzygium aqueum (Burm.f.) Alston Prevents Streptozotocin-Induced Pancreatic Beta Cells Damage via the TLR-4 Signaling Pathway - Mona F. Mahmoud; Shimaa Abdelaal; Heba Osama Mohammed; Assem M. El-Shazly; Rachid Daoud; Mohamed A. O. Abdelfattah; Mansour Sobeh (Frontiers Media S.A., 2021)
Although several treatments are available for the treatment of type 2 diabetes mellitus, adverse effects and cost burden impose the search for safe, efficient, and cost-effective alternative herbal remedies. Syzygium aqueum (Burm.f.) Alston, a natural anti-inflammatory, antioxidant herb, may suppress diabetes-associated inflammation and pancreatic beta-cell death. Here, we tested the ability of the bioactive leaf extract (SA) to prevent streptozotocin (STZ)-induced oxidative stress and inflammation in pancreatic beta cells in rats and the involvement of the TLR-4 signaling pathway. Non-fasted rats pretreated with 100 or 200 mg kg−1 SA 2 days prior to the STZ challenge and for 14 days later had up to 52 and 39% reduction in the glucose levels, respectively, while glibenclamide, the reference standard drug (0.5 mg kg−1), results in 70% reduction. Treatment with SA extract was accompanied by increased insulin secretion, restoration of Langerhans islets morphology, and decreased collagen deposition as demonstrated from ELISA measurement, H and E, and Mallory staining. Both glibenclamide and SA extract significantly decreased levels of TLR-4, MYD88, pro-inflammatory cytokines TNF-α, and TRAF-6 in pancreatic tissue homogenates, which correlated well with minimal pancreatic inflammatory cell infiltration. Pre-treatment with SA or glibenclamide decreased malondialdehyde, a sensitive biomarker of ROS-induced lipid peroxidation, and restored depleted reduced glutathione in the pancreas. Altogether, these data indicate that S. aqueum is effective in improving STZ-induced pancreatic damage, which could be beneficial in treating type 2 diabetes mellitus.